ORGANIZATION OF THE BUKHARA EMIRATE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The Ashtar Khanate ruled the territories of Transoxiana and Bukhara from the beginning of the 17th century to the middle of the 18th century. Although the representatives of this dynasty tried to continue the political legacy of the Shaybanid state, over time the internal and external situation of the state became more complicated. As a result, by the first half of the 18th century, a deep political and economic crisis occurred in the Bukhara Khanate. This situation led to the weakening of the power of the Ashtar Khanate and, ultimately, the rise of the Mangid dynasty to power.
Keywords: In the final stage of the Ashtar Khanate era, the central government weakened significantly. The position of the khans in governing the country decreased, and the influence of large officials and tribal leaders increased. Provincial governors began to pursue an independent policy, not submitting to the central government. As a result, state administration was disrupted and fragmentation increased in the regions of the country.